(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2017)
In the paper the functioning of nominative parenthetic sentences in the scientific and journalistic styles is analyzed. The authors have nominated them as syntactical isolated constructions of the basic sentence. These items are both substantives in the Common Case and complicated constructions with basic substantive in the same Case. Ukrainian linguists establish the fact of various usages of these constructions, their peculiarities greatly concerned with affirmation establishing items or phenomena existence. But their distinctive feature means understanding them as a part of the Present Tense because of the absence of syntactical verbs constructions used in special tenses or verbs voice. The paper shows that the nominative parenthetical sentences have the similar usage as nominative ones, e.g., in the limits of basic sentence they transform the data with the statement of available necessary items, but they must be followed by the detailed feature. Nominative sentences predication is illustrated by affirmation intonation. The authors have determined that nominative parenthetic sentences in the scientific and journalistic styles of Ukrainian literary language may give additional, exact functions to the basic sentence as follow: 1) affirmation about the subject of some activity (nominative parenthetic sentence names the performer, in the basic sentence it is called partly); 2) affirmation about the feature existence (nominative parenthetic sentence names the feature, with the feature so characteristic of the basic sentence); 3) local affirmation (nominative parenthetic sentence points to the component of basic sentence location). The main nominative component function can be performed by an item with numeral meaning. Nominative parenthetic sentences are often used both in journalistic and scientific texts to the identification of another text portion, especially for the identifications the text with its author (identification feature) or with the source of other text. The paper shows that the structure of nominative parenthetic sentences is the substantive lexical words in the basic form or the construction with the basic substantive in the Common Case.